Production model based on lean manufacturing and TPM to increase efficiency in a company in the textile sector - Alcazar Zamora, Piero Andre (2024)
The textile industry has been a participant in a global transformation, where the use of new technologies and tools achieve greater effectiveness within the organization. However, the management of these tools in the MYPES, who represent 99% of textile clothing in Peru are scarce, which reveals the various problems that affect the production efficiency of this sector, where the main problems are waste and production cycle times. That is why the purpose of this paper is to develop an improvement system through Lean Manufacturing and TPM tools, under the PDCA methodology, which increases the productive efficiency of a Peruvian textile company. Likewise, the execution of the improvement proposal will be validated through the Arena simulator software; where positive results were obtained, with an increase in productive efficiency by 42%.